Umbilical Cord Milking: A Review - Katheria, Anup C. (Frontiers in Pediatrics, 2018)
This is a review of umbilical cord milking, a controversial technique where the umbilical cord is squeezed several times before it is clamped an cut. While not physiological or natural for newborns, the question lies as to whether it is useful in certain circumstances, namely the depressed newborn. Here we review the literature and discuss why it could be considered as an alternative for the current practice of delayed cord clamping.